Estrus synchronization of cattle in Kansas - Simms, D.D.; Sprott, L.R.; Odde, Kenneth G.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
In 22 field trials involving 1,692 cattle, we evaluated Lutalyse as an estrus-synchronization agent for both natural mating and artificial insemination. Only 52.7% of the females in all 22 trials were cycling at the start of the breeding season. Both body condition and days postpartum at the start of the breeding season influenced the response to Lutalyse. First-service pregnancy rate in the 2 or 3 days of synchronization was 38.4% for all 453 females bred artificially in 12 trials in northwestern Kansas. The rate was 59%, however, if only females observed to be in heat were counted; but only 24.5% if only those in which no heat was observed were counted.
Keywords: Beef; Lutalyse; Estrus